A comprehensive mechanistic model for simulating algal growth dynamics in photobioreactors. (June 2017) - Shriwastav, Amritanshu; Thomas, Jeenu; Bose, Purnendu
Highlights: A comprehensive mechanistic model of algal growth in photobioreactors is developed. Model incorporates state-of-the-art understanding of algal system. Model is able to simulate the independent experimental data and complex processes. It provides a potential tool for investigating complex relation between processes. Abstract: A comprehensive mechanistic model for describing algal growth dynamics in a photobioreactor was developed in this work with state of the art understanding and realistic assumptions for major associated processes. The model included 27 state variables related to various algal processes. This model was validated with extensive experimental data obtained from independent growth experiments in batch reactors, and was able to simulate system performance reasonably well. The comprehensive nature of the formulation also highlights the complex inter-relationship between all processes, and provides a tool for gaining more systematic insights into algal behavior in photobioreactors and other such systems.